The Effect of Project-Based Learning through YouTube Presentations on English Learning Outcomes in Physics - Edi Rozal; Rizki Ananda; Aminah Zb; Mohammad Fauziddin; Fauzan Sulman (STAI Hubbulwathan Duri, 2021)
This study aims to analyze the effect of project-based learning with YouTube presentations as a final project on the cognitive domain online learning outcomes in English for Physics subjects. This study used a quantitative approach with a quasi-experimental method. The design of the study was post-test with a non-equivalent design. The populations of this study were the fourth-semester students of Physics Tadris, which amounted to 32 people. The samples were taken by using the saturated sampling technique. The instrument used in this study was 20 multiple-choice questions. in analyzing the data, the researcher used the t-test and correlation test (phi (Φ) test) with a significance level of α = 0,05. The results of the t-test show that there is a difference in learning achievement where the experimental class is better than the control class. Then from the results of the correlation test (phi test (Φ)) shows that project-based learning with YouTube achievement as a final project has a significant effect on the cognitive domain.